Exploring the Drivers of Home Births: Perspectives, Risks, Benefits, and Policy Implications in Zamboanga Sibugay, Philippines - Modillas, Marichu B.; Oliva, Dave L.; Opada, Lynne Leah M.; Gallego, Randy Ian (Journal of Maternal and Child Health, 2024)
Background: The persistence of home births in the Philippines remains conspicuous, despite the enforcement of policies discouraging this practice and the prevailing concerns about its safety. This research aims to delve into the various perspectives of women concerning home births to describe the underlying motivations behind their choices, their perceptions of the associated risks and benefits, and their stance on the “no home-birthing policy” of the state. Subjects and Method: This was a descriptive, cross-sectional study involving 80 mothers drawn from Malangas, Zamboanga Sibugay, Philippines through a referral-based sampling method. The study examined sociodemographic characteristics as independent variables, while dependent variables included perceived reasons for home birth preference, associated risks and benefits, and respondents' views on the "no home-birthing" policy. Data were described in descriptive statistics. Results: The findings showed that the inclination of women toward giving birth at home without the presence of professional birth attendants emanates from a multitude of factors. These include economic considerations, the sense of a familiar and comfortable environment, deeply rooted cultural beliefs, challenges related to accessibility to health facilities, and geographical impediments. Notwithstanding the inherent health risks, women opt for home births due to cost considerations, improved accessibility, and as a means of expressing their cultural and personal convictions. Consequently, the "no home-birthing policy" implemented in the Philippines is seen to reflect an effort to safeguard maternal and neonatal health by promoting facility-based deliveries. Conclusion: The study underscores the importance of developing a holistic healthcare strategy that harmonizes women's autonomy and cultural practices with the crucial goal of ensuring safe childbirth, especially in marginalized areas.